(untitled) (International Journal of Contemporary Security Studies, 2022)
Vast number of studies on educational institutions tend to provide an overview of the state-of-play of key security dimensions, practices and challenges for schools and their actors. The publication “Security in the Educational Institutions in Serbia” presents one of the contributions to the existing body of knowledge. This thematic proceeding is issued by the Faculty of Security Studies of the University of Belgrade, as a result of the scientific project “Security and protection of the educational system management and function in Serbia (basic information, principles, protocols, procedures and tools)”. Edited by Zorica Stanimirović and Aleksandra Ilić, this publication brought to the fore all relevant aspects of problem analysis in educational institutions in Serbia.